(untitled) (De Musica, 2025)
The operetta-parodia Orfee in vioron by Cletto Arrighi, while drawing inspiration from Jacques Offenbach’s Orphée aux Enfers, does not merely reinterpret the French original but becomes a vehicle for satire against the so-called musica dell’avvenire, particularly Wagnerian music. Through an analysis of contemporary newspaper sources and the autograph manuscripts of the libretto, this study aims to reconstruct the production context of the work and its reception, highlighting the reasons for its resounding failure. Both the audience and critics reacted negatively to the performance, emphasizing its lack of originality and the poor quality of its musical execution. Nevertheless, Arrighi’s work fits into a broader tradition of Milanese satirical theater, which draws on references to popular culture and the aesthetic-musical debate of the time. The analysis of the dramaturgical and musical structure of Orfee in vioron reveals the complex relationship between the French operetta tradition and Italian musical culture, raising questions about the reception of German music in Italy. Despite the opera’s failure, its value as a historical document and a reflection of the artistic tensions of the time remains undeniable.